Knowledge, attitude, and practice of oral health care personnel regarding airborne spread of infection in Davangere, India - B Pai; G M Prashant; Ramya Shenoy; G N Chandu (Wolters Kluwer Medknow Publications, 2014)
Introduction: Oral health care professionals (OHPs) are population with a high risk of infections, as they are exposed to an array of microorganisms in saliva and other body fluids during treatment. The aerosolized oral fluids during treatment may form a potent pool of infection. Objective: The objective was to assess the knowledge, attitude, and practice (KAP) about airborne infection and their precaution among OHPs in Davangere, India. Materials and Methods: A cross-sectional study was carried out in two dental teaching institutions of Davangere. The questionnaire contained questions related to KAP on airborne infection, its spread, and precaution. All the scores were summed and reported on a scale of 0-9 for knowledge, 0-4 for attitude and practice questions were scored on a 5-point Likert-Scale. Result: A response rate of 95.27% was observed. All the respondents knew that the infection was spread through aerosols during treatment. There was a significant improvement in KAP as the years in clinical practice increased. There was a linear correlation between knowledge and attitude (r = 0.171, P < 0.001), and knowledge and practice scores (r = 0.142, P < 0.00l) when all groups (dental faculty, postgraduate, and students) were combined, but there was no correlation between attitude and practice scores of individuals. Conclusion: This study reflects an increased knowledge and practice as the professionals move higher in the hierarchy. But there exists some disparity between the isolation precautions followed by the respondents of the current study and those from the recommended guidelines.